Sistem Informasi Geografis Pemetaan ODP (Optic Distribution Point) Berbasis Android - Rahmat Yusuf (Jurnal Cosphi, 2019)
This study aims to make an application of ODP (Optic Distribution Optic) Mapping Geographic Information System in Lekobalo Bebek Andorid District. By utilizing MySQL as a database, as well as the programming language PHP and Google Maps to display the ODP (Optic Distribution Point) location map in the form of an Android smartphone application. Based on this research, we can find out the location of the ODP in Lekobalo District. From the purpose of this study the researchers took the problems that are often faced by technicians in finding ODP locations and now the application aims to solve the problems faced by technicians. This study uses a combination of spatial and non-spatial methods and Waterfall methods: both in the form of location coordinates, photos, maps of the sub-district location Waterfall method itself has several stages, namely: analysis, system design implementation, integration, operation and maintenance. as the research itself. The results of this study are the making of Android smartphone-based applications, of course some items in the application are in the form of ODP list, ODP map location, application and application logout application testing shown to the user initial display design application running the application through the results of Android phones that expect to display the beginning of the application, then the action that is executed selects the existing icons and presses the buttons on the icons and the results are expected to be able to display the selected icon choice of the user. Based on what has been described a number of conclusions, namely: ODP (Optic Distribution Optic) mapping system with mobile-based mapping that allows users to find locations, with this application media allows users to find out which ODP location users want to search for online access using Andorid. Suggestions needed in this research are criticism and input to build this application more desirable. Keywords: Geographic Information System Based on Android, MySQL, PHP, Waterfall and Spatial Non Spatial Programming.